2003
DOI: 10.1001/archneur.60.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Drop Attacks and Vertigo Secondary to a Non-Meniere Otologic Cause

Abstract: Background: Tumarkin falls are sudden drop-attack falls that occur in a subset of patients with Meniere syndrome (endolymphatic hydrops), an inner ear disorder characterized by vertigo spells and hearing loss. Objective: To describe the clinical features and quantitative audiovestibular testing results in a case series of patients with Tumarkin falls, episodic vertigo, and normal hearing. Setting: University referral center for disorders of balance and hearing. Methods: Case series (unselected) of all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 23 publications
1
32
0
3
Order By: Relevance
“…Furthermore, each patient characteristically fell in the same direction (i.e., patient 5 fell to the left, and patient 6 fell to the right), which was seldom occurred in vertebrobasilar insufficiency. Ishiyama et al [7] reported 6 patients with drop attacks typical of Tumarkin falls and normal hearing as in our last two patients. Presumably, the mechanism of the sudden falls in these patients is a peripheral vestibular phenomenon as in Ishiyama et al's cases.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, each patient characteristically fell in the same direction (i.e., patient 5 fell to the left, and patient 6 fell to the right), which was seldom occurred in vertebrobasilar insufficiency. Ishiyama et al [7] reported 6 patients with drop attacks typical of Tumarkin falls and normal hearing as in our last two patients. Presumably, the mechanism of the sudden falls in these patients is a peripheral vestibular phenomenon as in Ishiyama et al's cases.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, we know of only one prior study of Tumarkin vestibulopathy with normal hearing [7]. Thus, we present 6 consecutive cases of elderly patients who had sudden falls typical of Tumarkin fall associated with (4) or without (2) hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…Another uncontrolled case series also found an increased prevalence of migraine among MD patients [35], although a questionnaire-based survey found a nonsignificant decrease in prevalence of migraine [36]. Migraine has also been associated with the falls attributed to the otolithic crises of Tumarkin, which are the sudden drop-attacks that have been noted in some patients with MD [37]. A partial explanation for the frequent concurrence of MD and migraine is that some patients may fit the diagnostic categories for both.…”
Section: Auditory Symptoms and Ménière's Diseasementioning
confidence: 99%
“…These events are often described as 'otolithic catastrophes' [Tumarkin, 1936], 'Tumarkin otolithic attacks' or simply Tumarkin attacks (TA). DA are not exclusive to patients with MD as they also occur in patients with other peripheral vestibular disorders [Ishiyama et al, 2003;Brantberg et al, 2005;Lee et al, 2005].…”
Section: Introductionmentioning
confidence: 99%